2002
DOI: 10.1097/00005537-200211000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Implication of 18F‐Fluoro‐2‐Deoxy‐D‐Glucose Positron Emission Tomography on Management of Carcinoma of Unknown Primary in the Head and Neck: A Danish Cohort Study

Abstract: With our present strategy of wide-field irradiation in patients with neck node metastases from a carcinoma of unknown primary, whole-body 18F-FDG PET had treatment-related implications in 24% (10 of 42) of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
0
9

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(54 citation statements)
references
References 18 publications
3
42
0
9
Order By: Relevance
“…This explains the reported differences in the accuracy for FDG-PET applied in the search for the primary tumor site. In our study, 11 primary tumors corresponding to a success rate of 52% were correctly identifi ed similar to previous reports [4,[11][12][13][14][29][30][31][32][33][34] .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This explains the reported differences in the accuracy for FDG-PET applied in the search for the primary tumor site. In our study, 11 primary tumors corresponding to a success rate of 52% were correctly identifi ed similar to previous reports [4,[11][12][13][14][29][30][31][32][33][34] .…”
Section: Discussionsupporting
confidence: 89%
“…In contrast FDG-PET is superior in locating CUP with varying detection rates from 23% up to 90% depending on the preselected patient population [4,[11][12][13][14][29][30][31][32][33][34] . As until now, no consensus has been established on how routine clinical workup should be done in patients with CUP.…”
Section: Discussionmentioning
confidence: 99%
“…FDG-PET has proved to be a complementary study for patients with unknown primary tumor of the head and neck when conventional evaluation fails (Fig 2). [11][12][13][14][15][16][17][18] A review of 16 studies published between 1994 and 2003 evaluating the utility of FDG-PET in identifying unknown primary carcinomas af- PET/CT showed a 1.0 ϫ 1.2 cm hypermetabolic (gold arrow) and enhancing (red arrow) lesion at the right base of the tongue, large nodes in the right levels II/III, an 8-mm node at level IV, and no left-sided nodes or distant metastases. Direct laryngoscopy with biopsy and cervical esophagoscopy showed no lesions, but palpation showed a 1-cm firm right base of tongue lesion not crossing the midline, which was pathologically proved to be SCC.…”
Section: Detection Of Unknown Primary Tumormentioning
confidence: 99%
“…larynx, and upper esophagus), anatomic imaging with CT and/or MRI, and blind tongue base biopsy. Numerous studies have addressed the ability of PET to identify primary locations after traditional work-up [29][30][31]. A meta-analysis by Rusthoven and colleagues [32] showed that PET was able to recognize a primary tumor after negative conventional work-up in one quarter of patients with an overall sensitivity and specificity of 88% and 75%, respectively.…”
Section: Unknown Primary Tumorsmentioning
confidence: 99%